Trends in maternal mortality in Latin America and the caribbean: a joinpoint analysis - Quiroz Acuña, Linda (2025)
Background Maternal mortality remains a significant public health issue in low- and middle-income countries (LMICs), with high incidence rates in Latin America and the Caribbean (LAC). While maternal mortality decreased by nearly 45% between 1990 and 2015, regional inequalities persist. This study assesses maternal mortality trends in LAC women from 1997 to 2019, providing key insights to address this issue. Methods An ecological observational time-series study was conducted using data from the WHO Mortality Database for 18 countries in Latin America and the Caribbean between 1997 and 2019, focusing on women aged 15–49 years. Age-standardized maternal mortality rates (ASMR) per 100,000 person-years were estimated using the direct method, based on the SEGI world standard population. The MMR, defined as maternal deaths per 100,000 live births, was calculated using data from the Pan American Health Organization (PAHO). Trends were analyzed using Joinpoint regression to estimate the Annual Percentage Change (APC) and Average Annual Percentage Change (AAPC), with p < 0.05 indicating statistical significance. Results The highest maternal mortality rates in 1997 were reported in Guatemala, Nicaragua, and Paraguay, while by 2019, Venezuela, the Dominican Republic, and Paraguay had the highest rates. Similarly, the highest maternal mortality ratios (MMRs) in 2019 were observed in Venezuela, the Dominican Republic, and Paraguay. Joinpoint regression identified significant annual reductions in maternal mortality rates in seven countries—particularly Nicaragua (AAPC: −6.7%) and Guatemala (AAPC: −4.2%)—while Venezuela exhibited a significant increase (AAPC: +5.3%). Regarding MMR trends, the most notable improvements were seen in Nicaragua (AAPC: −4.5%) and Costa Rica (AAPC: −2.0%), whereas Brazil, Puerto Rico, and Venezuela experienced significant upward trends. Conclusions Despite overall progress, regional differences in maternal mortality persist across Latin America and the Caribbean. These variations highlight the importance of strengthening maternal health systems, improving access to skilled birth attendance, and ensuring quality prenatal and postnatal care. Future studies should explore underlying contextual and structural factors driving these trends and promote the use of disaggregated data to inform equitable health policies.